Assessment of visitor perceptions and economic valuation of Tengket Beach attractions - Fauziyah, Elys; Lestari, Fany Etana (Publisher of Widyagama University of Malang (UWG Press), 2023)
Tengket Beach has an unspoiled beauty, with stretches of fine white sand as the main visitor attraction. However, the village government and surrounding communities have not been interested in managing this potential. Therefore, this study aimed to determine visitor perceptions, the factors influencing the number of visits, and Tengket Beach tourismâ€™s economic value. Samples were determined using the linear time function formula. The data collected were further analyzed by descriptive qualitative, multiple linear regression, and travel cost methods. The results showed that Tengket Beach is perceived as unattractive based on its accessibility and facilities. Based on accessibility indicators, 96.7% of visitors stated that Tengket Beach was not feasible. Meanwhile, based on facility criteria, only 20% of visitors stated that the place had good facilities. Other findings show that most visitors explained that the beach is quite interesting regarding its attractiveness. The results also showed that travel costs negatively affect visits, while accessibility and facilities have a positive effect. Additionally, the economic value of the beach is IDR5,890,560,000 per year. This is an indicator that Tengket Beach has the potential to be used as an economic resource for the surrounding community.JEL ClassificationÂ C26; I26; Q51